Hot cold tumbler - Robin, Lee Chiap Loong (2016)
The project Hot Cold Tumbler aims to heat and cool drinking water without using wired electrical supply. With a single selection on the button, users are able to make the favorite hot or cold drinks and it is portable. Hence, it's applicable to use even on high terrain or during camping. The general operation of the bottle is using thermoelectric chip which serves as the heater/cooler pad and LiFeP04 batteries which are rechargeable and energy efficient as power supply. The temperature is regulated and controlled by both systems. The power supply is rechargeable. The bottle is ideal for people of all walks of life and especially to mothers. This project is intended to help housewives to reduce the tasks of transferring hot water into thermo flask for further usage and prepare cool water to hydrate us when the weather is hot.